Contemporary legal environment of the agricultural real estate market – the main regulatory areas - Czechowski, Paweł; Marciniuk, Konrad (Przegląd Prawa Rolnego, 2021)
The aim of this paper was to analyse the main areas of contemporary legal regulation of agricultural real estate market which affect both the legal situation of the agricultural real estate owner and the contemporary shape of agricultural market. The authors conclude, among other things, that state interference, especially in the public law sphere, violates the constitutional limits of property protection as it significantly depletes the right of owner's freedom of action. The existing regulatory restrictions violate clearly the balance in the regulation of agricultural property understood as a complex of rights and obligations. The emerging normative primacy and domination of legal instruments of intervention in the agricultural real estate market available in administrative law limit the occurrence of civil law instruments in favour of administrative law instruments.